Batak ulos ethnomathematics exploration based on geogebra software - Sartika, Dewi; Saputra, Eri; Herizal (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
Ethnomathematics is a science that bridges mathematics and culture. One of the Toba Batak cultures that is related to mathematics is the traditional craft of Saddum ulos cloth which they use as clothing in rituals or series of birth, death and wedding events.  Toba Batak culture, in the form of traditional Saddum Ulos cloth crafts, is interesting to reveal and explore through ethnomathematics based on Geogebra software. Therefore, the aim of this research is to analyze the mathematical concepts contained in Saddum ulos cloth and the use of Geogebra software in making the motifs. The research method used was a descriptive method with an ethnographic approach. The data sources were obtained from interviews, observation and documentation. Data were analyzed through triangulation of data sources and descriptive methods. The research results show that Saddum ulos batik has mathematical concepts such as lines and angles, number patterns, plane geometry, and geometric transformations. Making the Saddum ulos motif using Geogebra makes the Saddum ulos motif better visualized and its relationship with mathematics clearly illustrated.